Clinico- haematological spectrum of females with inherited Bleeding Disorders - Nadeem Ikram, Nadeem Ikram; Tahira Zafar, Tahira Zafar; Arshad Ali Sabir, Arshad Ali Sabir; Khalid Hassan, Khalid Hassan; Samina Zamanat, Samina Zamanat (Journal of Rawalpindi Medical College, 2010)
Background: Inherited bleeding disorders in females are under-diagnosed, eventually leading to multiple problems. This situation is further worsened by the inadequate information , non – availability of diagnostic facilities and low awareness on the clinical side Methods: In this non – interventional descriptive study , females with inherited bleeding disorders were assessed. Clinical presentations, demographic data and management received was recorded. Complete blood counts, prothrombin time, activated partial thromboplastin time, thrombin time and platelet function studies were performed, where required.. Results: In all the patients with inherited bleeding disorders , females constituted 16.85%. von Willebrand disease was the commonest (50.84%) out of all inherited bleeding disorders in females. In rest of the females autosomal recessive coagulation defects and platelet function defects constituted 25.42% and 23.72%, respectively. Majority of the females (83.04%) were below 17 years of age. Menorrhagia (46.87%) was the commonest clinical episode. Spontaneous bleed was seen in 95% episodes. Majority of the episodes (94.14%) were soft tissue bleeding episodes and joint bleeds were minimal (5.68%). Tranexamic acid was the most commonly used therapeutic agent . Surgical intervention was employed in 18 episodes. Conclusion: Females with inherited bleeding disorders have severely impaired quality of life , fail to get proper management and go through unwanted surgeries ( D&C; Hysterectomies).